Marino, S., Roosblad, J., & Penninx, R. (Eds., 2017), Trade Unions and Migrant Workers: New Contexts and Challenges in Europe, Cheltenham: Edward Elgar Publishing. - Carlotta Benvegnù (Coordinamento SIBA, 2019)
For Book Reviews Abstract is not required